Clinicopathological Factors Determining the Pathological Response to Neoadjuvant Therapy in HER2 Positive Breast Cancer - Abdullah Evren YETİŞİR; Semra PAYDAŞ (Namık Kemal Tıp Dergisi, 2021)

(untitled)
Aim:In our study, we aimed to determine the clinicopathological factors affecting the pathological response after neoadjuvant chemotherapy in HER2 positive breast cancer.Materials and Methods:A total of 54 HER2 expression positive cases were included in this study. Neoadjuvant chemotherapy regimen containing trastuzumab was applied to all patients. Patients’ age, gender, disease stage, tumor size and lymph node status, estrogen and progesterone receptor status, Ki-67 proliferation index, tumor grade, menopausal status and pathological complete response status after neoadjuvant therapy, neoadjuvant treatment regimen and the relationship between the tumor and histological subtype were examined.Results:Grade III tumor, hormone receptor negativity, high Ki-67 score, and the presence of T3 or T4 tumor were found to be better associated with pathological complete response (p=0.036, p=0.033, p=0.021, p=0.048, respectively). High tumor grade, hormone receptor negativity and high Ki-67 score were found as independent risk factors determining pathological complete response (p=0.043, p=0.047, p=0.035, respectively).Conclusion:In this series of 54 cases with HER2 positive breast cancer, the parameters determining pathological complete response after neoadjuvant treatment are high Ki-67 proliferation index, grade III tumor and hormone receptor negativity.